LITERACY LITERATURE LEARNING WITH LET’S READ APPLICATIONS IN THE PANDEMIC ERA - Nur Samsiyah; V Teguh Suharto; Endang Sri Maruti (JURNAL HANDAYANI PGSD FIP UNIMED, 2020)
Abstract: One of them is literacy learning by using Android-based Let's Read to answer the challenges of the growing industrial era. In the midst of the rise of students using Android as a medium of communication, teachers need to change learning in and outside the classroom into interesting learning by utilizing computer media, mobile phones as literary literacymaterial. So that literary literacy is not monotonous, it must be in the library by choosing books in turns or by listening to the teacher's story on the page as a habit that only contains short stories in the book . By using the Let's Read application the teacher can give nuances of literary learning to be more often literary literate both at home and at school.Keywords: Literacy literature, Let’s ReadAbstrak: Salah satunya adalah pembelajaran literasi dengan menggunakan Let's Read berbasis Android untuk menjawab tantangan era industri yang berkembang. Di tengah maraknya siswa menggunakan Android sebagai media komunikasi, guru perlu mengubah pembelajaran di dalam dan di luar kelas menjadi pembelajaran yang menarik dengan memanfaatkan media komputer, ponsel sebagai bahan literasi sastra. Agar literasi sastra tidak monoton, di perpustakaan harus memilih buku secara bergantian atau dengan mendengarkan cerita guru yang berisi cerita pendek dalam buku Dengan menggunakan aplikasi “Let’s Read”guru dapat memberikan nuansa belajar literasi, melek huruf menjadi lebih melek sastra baik di rumah maupun di sekolah.Kata kunci: Literasi sastra, Mari membaca